The effectiveness of Bulgarian bag exercises on some physical variables for students majoring in physical education (swimming course) Palestine Technical University – Kadoorie - Abdelrazeq, Bassam Hamdan; Ewedat, Rawan Aref (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the effectiveness of Bulgarian bag exercises on some physical among students of physical education specialization. The researcher used the experimental method by designing the two equivalent groups for their suitability to the nature of the study on a sample of (20) students from the Physical Education major at Kadoorie University, they were randomly distributed into two equal groups, a control group and an experimental group, and each of them consisted of (10) students, and the group was trained The control group using the regular (traditional) program and the experimental group using the Bulgarian bag exercises, and the results of the study showed that there were statistically significant differences for the experimental and control group between the mean pre and post measurements in favor of the post measurement, where the percentage of improvement in physical tests in the strength of the muscles of the trunk using, the flexibility of the trunk The speed characteristic strength of the arms muscles 10 seconds, the speed characteristic strength of the abdominal muscles 10 seconds, the muscle power of the arm and shoulder region, respectively (13%, 20%, 17%, 30%, 24%, 18%, 15%). As it is clear from the results of the study, the experimental group who used the Bulgarian bag exercises outperformed the members of the control group who applied the regular training program in the post-measurement, where the percentage change for the physical tests was: (strength of the muscles of the trunk using (18%), flexibility of the trunk (20%). The speed characteristic strength of the muscles of the arms 10 seconds (30%), the speed characteristic of the muscles of the abdomen 10 seconds (35%), the muscular ability of the arm and shoulder area (30%)). The study recommends the need to use modern tools and methods in training because of their significant psychological, physical and skill impact on the learning process and to conduct more studies on the use of the Bulgarian bag on various Sports Games.